Nurturing Novelty: Toulmin's Greenhouse, Journal Rankings and Knowledge Evolution. Issue 1 (15th November 2018) - Renwick, Douglas W.S.; Breslin, Dermot; Price, Ilfryn
Abstract : Reflecting on Toulmin's, 1972 conceptualization of the academic research process, we fast‐forward his thinking to the current climate of academic excellence and associated journal ranking lists . We argue that the formal and informal use of such rankings throughout the hierarchy of research institutions creates an artificial environment within which favoured 'branches' of knowledge continue to flourish at the expense of new conceptual saplings . This 'greenhouse' effect might result in the creation of a knowledge tree which is increasingly unfit to the external world for which it is intended . We thus step back and examine wider implications of these factors on the broader evolution of knowledge in the research process . In sum, we argue for a Toulminian explanation of the process by which journal ranking lists reduce academic innovation and creativity, bias academic selection and constrain dissemination processes in the academic community .